2023
DOI: 10.1002/joc.8123
|View full text |Cite
|
Sign up to set email alerts
|

Thunderstorm tracking in Northwest Europe for enhanced hazard preparedness

Abstract: The tracking of thunderstorms provides critical information on their frequency and behaviour for early warning, prediction and preparedness. Thunderstorm tracking has previously been constrained by the boundaries of a particular country or has focused on a particular category such as severe thunderstorms and mesoscale convective systems. However, less severe thunderstorms also pose a risk to life and property and occur more frequently and thus warrant inclusion in investigations of thunderstorm behaviour. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
1
1
0
Order By: Relevance
“…We found that the correlation between summer climatological mean of surface wind speed and composite mean of K (PW) index during thunderstorms is statistically significant at −0.31 (−0.33). While thunderstorms are commonly associated with strong winds (Hayward et al, 2023), our finding further shows that areas characterized by lower values of K and PW indices during thunderstorms tend to exhibit higher surface wind speeds. Planetary boundary layer height (PBLH) affects the vertical distribution of temperature and moisture, which in turn influences CAPE available and moisture supply for thunderstorm development.…”
Section: Conclusion and Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We found that the correlation between summer climatological mean of surface wind speed and composite mean of K (PW) index during thunderstorms is statistically significant at −0.31 (−0.33). While thunderstorms are commonly associated with strong winds (Hayward et al, 2023), our finding further shows that areas characterized by lower values of K and PW indices during thunderstorms tend to exhibit higher surface wind speeds. Planetary boundary layer height (PBLH) affects the vertical distribution of temperature and moisture, which in turn influences CAPE available and moisture supply for thunderstorm development.…”
Section: Conclusion and Discussionsupporting
confidence: 71%
“…With the adoptions of improved observation methods and sophisticated mesoscale numerical models, the properties (e.g., flash rate, storm size, convective intensity, vertical structure, and microphysics) as well as dynamic and thermodynamic environmental conditions for thunderstorms are gradually revealed (Hayward et al, 2023; Islam et al, 2020; Kunz, 2007; Ma et al, 2021; Romps et al, 2014; Zhang et al, 2022). Several previous studies highlight the role of meteorological conditions and stability indices as the main reference for potential forecast of occurrence or non‐occurrence of thunderstorms in local areas.…”
Section: Introductionmentioning
confidence: 99%